2016
DOI: 10.1038/srep26666
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Structural Transformation in Mono- and Bi-Layered Molybdenum Disulfide

Abstract: Mono- and multi-layered molybdenum disulfide (MoS2) is considered to be one of the next generation anode materials for rechargeable ion batteries. Structural transformation from trigonal prismatic (2H) to octahedral (1T) upon lithium or sodium intercalation has been in-situ observed experimentally using transmission electron microscope during studies of their electrochemical dynamics processes. In this work, we explored the fundamental mechanisms of this structural transformation in both mono- and bi-layered M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 71 publications
5
47
0
Order By: Relevance
“…In agreement with previous DFT studies, we find the H phase to be the ground state structure for all four materials 11,19,28,29,[53][54][55] . The total energy differences between this phase and both the T phase and the T mixed phase are given in Fig.…”
Section: A Neutral Monolayerssupporting
confidence: 92%
“…In agreement with previous DFT studies, we find the H phase to be the ground state structure for all four materials 11,19,28,29,[53][54][55] . The total energy differences between this phase and both the T phase and the T mixed phase are given in Fig.…”
Section: A Neutral Monolayerssupporting
confidence: 92%
“…Layered transition metal dichalcogenides (TMS2) have attracted extensive research interest due to their excellent electrical, chemical and optical properties [11,12]. Among these, monolayer molybdenum disulfides (MoS2) have been applied in rechargeable ion batteries, transistors and catalysts [13][14][15]. Its good catalytic activity and stability for HER make it one of the promising candidates to replace noble metals including ruthenium, iridium and platinum [16].…”
Section: Introductionmentioning
confidence: 99%
“…1. Sun et al [13] studied the origin of phase transformation between 2H-and 1T'-MoS2, and showed that electron doping destabilizes the crystal structure of the 2H-MoS2, thus causing its structural transformation into the 1T'-MoS2 phase. The 2H-MoS2 phase is the most common and stable crystal structure of MoS2 with a semiconducting character.…”
Section: Introductionmentioning
confidence: 99%
“…As the Li/Mg/Al atoms are adsorbed on the MoS 2 , charge transfer from the atoms to the MoS 2 occurs [42,67]. The amount of charge transferred from the atoms will increase with the increase of strength of the electric field, and the difference in the charge transfer at the different sites will decrease with increasing strength of the electric field.…”
Section: Resultsmentioning
confidence: 99%